Issue Brief: Engaging Civil Society in Supporting Research Use in Health Systems - Lavis, JN; McCutchen, Ben; Bopardikar, Ameya (My University, 2009)
An assessment of what is known about problems related to engaging civil society in supporting research use in health systems, options for addressing these problems, and key implementation considerations. The issue brief was an input to a stakeholder dialogue on the topic of engaging civil society in supporting research use in health systems.
Keywords: civil society; research; health systems